Analisis Tingkat Kerusakan Jalan Dan Dampak Terhadap Masyarakat Komplek Sona Pola Kelurahan Oepura Kota Kupang - Frans, John H.; Sir, Tri MW; Ramadani, Claudia Natalia (Universitas Nusa Cendana, 2025)
The impact of road damage is divided into several aspects, namely activity, comfort, economy, and public health. The purpose of the study was to determine the level of road damage and the impact felt by the community in the Sona Pola Complex, Oepura Village, Kupang City. The average PCI value along the Anggrek road section is 53.70 which means moderate conditions. The results of the research on the impact of road damage most felt by the community from the aspect of the activity, namely damaged road conditions slowing down travel with an average value = 4.72, from the comfort aspect, namely damaged road conditions resulting in accidents with an average value = 4.76, from the economic aspect, namely damaged road conditions requiring more vehicle maintenance with an average value = 4.72, and from the health aspect, namely damaged road conditions creating dust and pollution with an average value = 4.61 and the results of the Likert scale method analysis obtained the highest percentage index of 95.29%, road damage resulting in accidents and the lowest percentage index of 86.59%, namely damaged road conditions triggering emotional and psychologically disturbing motorists